Microfluidic solvent extraction, stripping, and phase disengagement for high-value platinum chloride solutions. (22nd December 2015) - Kriel, Frederik H.; Holzner, Gregor; Grant, Richard A.; Woollam, Stephen; Ralston, John; Priest, Craig
Abstract: Extraction, scrubbing, and stripping of Pt(IV) in microfluidic solvent extraction (microSX) chips were studied using a secondary amine as the extractant. Real-time efficiency of phase disengagement was precisely determined. The time-dependant platinum concentration in the aqueous phase could be fitted with a pseudo-first order rate equation for three different organic/aqueous phase ratios (0.6, 2.2, and 5.7) that were achieved using dissimilar channel cross-sections. Extraction equilibrium was achieved within several seconds (2–6 s) in agreement with the fast extraction rate expected for a diffusion-limited ion exchange mechanism and the microscopic dimensions involved. Aqueous phase derived from a precious metals refinery was also extracted successfully, demonstrating that the process is relevant to refinery conditions. Scrubbing reported negligible loss of platinum from the organic phase. Stripping revealed that longer contact times were necessary to achieve equilibrium (~12 s) compared with extraction. Phase disengagement efficiencies were precisely determined for the first time using an online and quantitative approach, revealing up to 2% inefficiency with a slight bias towards the organic phase being lost into the aqueous stream. Graphical abstract: Highlights: Platinum extraction, scrubbing, and stripping in a microfluidic chip. Extraction and stripping reached equilibrium between 2 and 13 s. Online measurement of phase separation showed ~98% efficiency.